Comparing The Earnings Response Coefficients of U.S. Multinational and Domestics Firms: The Use of Geographic Segment Reporting Information - Indra Wijaya Kusuma (The Indonesian Journal of Accounting Research, 2013)
Cheng, et al. (1994) compare earnings response coefficients of U.S. multinational and U.S. domestic firms and conclude that U.S. multinational firms show a weaker relationship between earnings and returns than U.S. domestic firms. Further Cheng, et al. argue that the weaker relationship of multinational firms is caused by information complexity experienced by multinational firms.This study uses geographic segment reporting information for providing empirical proxies for information complexity. The purpose is to test whether information complexity is a major factor in explaining the difference in the relationship between earnings and returns using linear and portfolio rank models.The empirical results support the hypotheses that proxies for information complexity are negative and statistically significant. Including the proxies for information complexity moderately increases the earnings response coefficients of the multinational firms.This study has several limitations, such as using pooling and cross-sectional regressions, ignoring firm-specific regressions [Teets and Wasley (1996)]. In addition, the study ignores country-specific factors in deriving proxies for information complexity. Future research should address these issues.